Walk, run, jump and learn: Interactive multimedia for teaching locomotor skills in primary schools - Yovhandra Ockta; U. Umar; Anton Komaini; Kamal Firdaus; P. Padli; M. Masrun (Research and Development in Education (RaDEn), 2024)
Technology drives the development of interactive and customizable learning media, catering to diverse learner needs. The learning media in locomotor motion educational game applications in PE learning is the result of this research. This research develops interactive learning media using Construct 2 software on locomotor motion material for third graders students. This research applies the Brog and Gall model of research and development (R&D), involving media experts, material experts, physical education (PE) teachers, and students. The practicality test engaged PE teachers from three distinct schools, yielding an impressive average score of 98.89%, indicative of excellent practicality. The development of Construct 2-based learning media has proven very feasible to be used as an interactive learning media to increase student interest and participation in locomotor motion learning, creating an attractive and relevant learning atmosphere with the demands of today's all-digital era.